Chemical Diagnostics From Bench to Bedside - L.S. Tang, Nelson; Poon, Terence; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Next Generation Sequencing: Chemistry, Technology and Applications, by P. Hui Application of Next Generation Sequencing to Molecular Diagnosis of Inherited Diseases, by W. Zhang, H. Cui, L.-J.C. Wong Clinical Applications of the Latest Molecular Diagnostics in Noninvasive Prenatal Diagnosis, by K.C.A. Chan The Role of Protein Structural Analysis in the Next Generation Sequencing Era, by W.W. Yue, D.S. Froese, P.E. Brennan Emerging Applications of Single-Cell Diagnostics, by M. Shirai, T. Taniguchi, H. Kambara Mass Spectrometry in High-Throughput Clinical Biomarker Assays: Multiple Reaction Monitoring, by C.E. Parker, D. Domanski, A.J. Percy, A.G. Chambers, A.G. Camenzind, D.S. Smith, C.H. Borchers Advances in MALDI Mass Spectrometry in Clinical Diagnostic Applications, by E.W.Y. Ng, M.Y.M. Wong, T.C.W. Poon Application of Mass Spectrometry in Newborn Screening: About Both Small Molecular Diseases and Lysosomal Storage Diseases, by W.-L. Hwu, Y.-H. Chien, N.-C. Lee, S.-F. Wang, S.-C. Chiang, L.-W. Hsu
Next Generation Sequencing: Chemistry, Technology and Applications, by P. Hui -- Application of Next Generation Sequencing to Molecular Diagnosis of Inherited Diseases, by W. Zhang, H. Cui, L.-J.C. Wong -- Clinical Applications of the Latest Molecular Diagnostics in Noninvasive Prenatal Diagnosis, by K.C.A. Chan -- The Role of Protein Structural Analysis in the Next Generation Sequencing Era, by W.W. Yue, D.S. Froese, P.E. Brennan -- Emerging Applications of Single-Cell Diagnostics, by M. Shirai, T. Taniguchi, H. Kambara -- Mass Spectrometry in High-Throughput Clinical Biomarker Assays: Multiple Reaction Monitoring, by C.E. Parker, D. Domanski, A.J. Percy, A.G. Chambers, A.G. Camenzind, D.S. Smith, C.H. Borchers -- Advances in MALDI Mass Spectrometry in Clinical Diagnostic Applications, by E.W.Y. Ng, M.Y.M. Wong, T.C.W. Poon -- Application of Mass Spectrometry in Newborn Screening: About Both Small Molecular Diseases and Lysosomal Storage Diseases, by W.-L. Hwu, Y.-H. Chien, N.-C. Lee, S.-F. Wang, S.-C. Chiang, L.-W. Hsu.
Keywords: Chemistry; Biochemistry; Proteomics; Microbial genetics; Chemistry; Medicinal Chemistry; Proteomics; Microbial Genetics and Genomics